Success Rate of Insertion and Postoperative Sore Throat: I-Gel Versus Laryngeal Mask Airway Classic - Pokhrel, Prakriti; Parajuli, Prastab (Med Phoenix, 2021)
Introduction: Supraglottic devices are a useful advent in airway management filling a gap between the facemask and tracheal tube in terms of both anatomical position and degree of invasiveness. Laryngeal mask airway classic (LMA-C) being first of its kind and I-gel is second generation non-inflatable supraglottic device. The objective of our study was to compare the two supraglottic devices, Laryngeal mask airway classic (LMA-C) and I-gel for a success rate of insertion and postoperative sore throat. Materials and Methods: A total of 80 patients scheduled for elective surgical procedures were studied in a prospective, randomly assigned, comparative and interventional manner. Patients were randomly allocated into two groups with forty patients in each group. I-gel and LMA-C were used in Groups 1 and 2 respectively. After achieving adequate depth of anesthesia the supraglottic device of appropriate size was inserted. The success rate of insertion of the device was represented by the number of insertion attempts. In the postoperative ward within 24 hours after surgery patient was asked whether a sore throat was present. Results: There was a statistically significant difference between the two supraglottic devices in terms of successful attempts of insertion (p-value 0.02).In group 1(I-gel)34 out of 40 patients had first attempt insertion success,6 patients in the second attempt, and no patient had third insertion attempt. In group 2 (LMA-C) first-time insertion success was in 14 patients, 23 patients in the second attempt, and 3 patients in the third attempt. The incidence of postoperative sore throat was higher in the LMA-C group than the I-gel group(17.5% vs 5% respectively) with a p-value of 0.154. Conclusion: Compared to the laryngeal mask airway classic, I-gel was inserted with less number of attempts and had a lower incidence of postoperative sore throat.